2019
DOI: 10.1016/j.opelre.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a broadband coherent supercontinuum generation in Ga8Sb32S60 chalcogenide photonic crystal fiber with all-normal dispersion

Abstract: All normal dispersion (ANDi) and highly nonlinear chalcogenide glass photonic crystal fiber (PCF) is proposed and numerically investigated for a broad, coherent and ultra-flat mid-infrared supercontinuum generation. The proposed PCF consists of a solid core made of Ga 8 Sb 32 S 60 glass surrounded by seven rings of air holes arranged in a triangular lattice. We show by employing the finite difference frequency domain (FDFD) method that the Ga 8 Sb 32 S 60 PCF dispersion properties can be engineered by carefull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Medjouri et al [30] Aparna et al [31] Pooja Chauhan et al [32] Pooja Chauhan et al [33] Mohit Sharma and Konar [34] Than Singh Saini et al [35] Proposed using the telecommunication wavelength of about 1.55 µm.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Medjouri et al [30] Aparna et al [31] Pooja Chauhan et al [32] Pooja Chauhan et al [33] Mohit Sharma and Konar [34] Than Singh Saini et al [35] Proposed using the telecommunication wavelength of about 1.55 µm.…”
Section: Parametersmentioning
confidence: 99%
“…The white light continuum is the first SC observed in a borosilicate glass [24]. The SC has become the most important achievement and it has several applications, such as pulse compressions in a nonlinear optical medium, optical fiber communication, spectroscopy using ultrafast laser pulses, generation of the frequency comb, optical coherence tomography and metrology [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…PCFs provide a large degree of freedom in tailoring the dispersion characteristic by changing the size and pattern of air holes in the cross-section such as using double-clad structures or infiltration of different materials which provide tenability. [15,[18][19][20] On the other hand, waveguides provide integration, and hence, different types of waveguides have been considered for SCG, so far. [21][22][23][24] Recently, chalcogenide (ChG) glasses composed of the chalcogen (S, Se, and Te) and metalloid (Ge, As, Sb, and Ga) elements have attracted the attention of scientists in mid-infrared (Mid-IR) SCG [25][26][27] due to its appealing features such as lower two-photon absorption, high resilient to crystallization, higher Kerr coefficient (≈200 times higher than SiO 2 ), higher linear refractive index, and wide spectral transparency compared to fluoride, [28] tellurite, [29] and lead silicate.…”
Section: Doi: 101002/andp202100226mentioning
confidence: 99%
“…Seven rings of air holes arranged in a hexagonal lattice surround the Ga 8 Sb 32 S 60 . Simulations showed that the wavelength range from 1.65 μm to 9.24 μm at 20 dB in this structure was broadband and completely (Medjouri et al 2019). For more, a type of Chg AsSe2 for broadband MIR light source was designed.…”
Section: Introductionmentioning
confidence: 95%
“…All normal dispersion and nonlinear Chg glass were recently studied (Medjouri et al 2019). Seven rings of air holes arranged in a hexagonal lattice surround the Ga 8 Sb 32 S 60 .…”
Section: Introductionmentioning
confidence: 99%